Pelatihan Logika Pemrograman bagi Guru SD Muhammadiyah Jasem Ngoro Mojokerto Berbasis Game Scratch - Hindarto Hindarto; Ade Eviyanti; Sumarno Sumarno; Donni Adeleo Ardana; Abdul Haris Setya Nugraha (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This Community Service program aims to improve the digital literacy and computational thinking skills of elementary school teachers through game-based programming algorithm training using the Scratch platform. The problems faced by partners are teachers' limited understanding of programming algorithm concepts and the minimal use of interactive technology-based learning media in the learning process. The This Community Service program activity was carried out at Muhammadiyah Jasem Ngoro Elementary School in Mojokerto using a participatory and hands-on training method, which included needs analysis, module development, training implementation, and program evaluation. To measure the effectiveness of the activity, pre-test and post-test instruments were used that examined aspects of digital literacy, computational thinking, understanding of basic algorithms, and mastery of Scratch. The evaluation results showed significant improvements in all aspects measured, where teachers not only understood algorithm concepts conceptually but were also able to develop simple educational games relevant to elementary school learning. This program had a positive impact on improving teacher competence, confidence, and readiness in integrating technology-based learning. Thus, the Scratch-based programming algorithm training is effective as an effort to strengthen the digital literacy and computational thinking of elementary school teachers.